2010
DOI: 10.1007/s10765-010-0744-6
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Specific Heat Capacity Functions of Polyvinyl Alcohol–Cassava Starch Blends

Abstract: The specific heat capacity (C sp ) of polyvinyl alcohol (PVOH) blends with cassava starch (CSS) was studied by the differential scanning calorimetry method. Specimens of PVOH-CSS blends: PPV37 (70 mass% CSS) and PPV46 (60 mass% CSS) were prepared by a melt blending method with glycerol added as a plasticizer. The results showed that the specific heat capacity of PPV37 and PPV46 at temperatures from 330 K to 530 K increased from (2.963 to 14.995) J · g −1 · K −1 and (2.517 to 14.727) J · g −1 · K −1 , respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Higher concentrations of amylose present better mechanical properties in relation to structure with a high content of amylopectin, comments the author, which still asserts a more practical and economic use of a blend with higher amount of starch. In this sense, Sin et al [67] showed through FT-IR analysis that the hydrogen bonds between PVA and starch are stable, and the high concentration of PVA in relation to starch makes the system more stable and compatible. The mechanical behavior, analyzed as a whole considering the TB, showed that the blend 80P20A presented the best result once the elongation Analyses have showed (Fig.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Higher concentrations of amylose present better mechanical properties in relation to structure with a high content of amylopectin, comments the author, which still asserts a more practical and economic use of a blend with higher amount of starch. In this sense, Sin et al [67] showed through FT-IR analysis that the hydrogen bonds between PVA and starch are stable, and the high concentration of PVA in relation to starch makes the system more stable and compatible. The mechanical behavior, analyzed as a whole considering the TB, showed that the blend 80P20A presented the best result once the elongation Analyses have showed (Fig.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Although glycerol (Gl) has been commonly used as a polymer plasticizer [24][25][26], some researchers have studied the effect of glycerol addition on the electrical properties of polymers. Based on impedance analysis, Ayala et al reported that the DC conductivity of cassava starch biopolymer was very sensitive to glycerol addition up to 50 wt% [27].…”
Section: Introductionmentioning
confidence: 99%